As nanotecnologias no panorama regulatório: entre a ausência de regulação estatal específica e a necessidade de harmonização regulatória não estatal - Wilson Engelmann; Ronei Leonardo Pulz (Araucaria)
This paper investigates the development of nanotechnology, as an example of so-called “new technologies” that promise to revolutionize human life on earth. The ethical and legal norms of the nano-scale results are still preliminary, although they are absolutely necessary. The aim is to highlight the importance of participation of law, as an area of Impacts of Science, in this scenario of innovation. There is a legislative difficulty of regulating the matter. The article points out the dialogue between the sources of law as a new way to develop legal responses to nanotechnology, from the normative productions generated by international agencies and organizations, which are already issuing recommendations, standards and guidelines, as new forms of regulation, which should be harmonized, given the large amount of these texts already available.